1972
DOI: 10.1128/aac.2.5.395
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral Action of Camptothecin

Abstract: At a concentration of 10 m, camptothecin inhibited vaccinia deoxyribonucleic acid (DNA) synthesis in HeLa cells. Inhibition of viral DNA synthesis was observed when the drug was added before infection or at 1 or 2 hr after infection. Inhibitory effects of camptothecin on vaccinia DNA synthesis could be reversed, even after exposure to the alkaloid for 2 hr. Viral DNA, isolated from vacciniainfected, camptothecin-treated cells, displayed an altered sedimentation constant after alkaline sucrose density gradient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

1977
1977
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…A role of the poxvirus topoisomerase in homologous DNA recombination is also unlikely on the grounds that late gene expression is not required (28,35). Our experiments do not exclude a role for a cellular topoisomerase in transcription or replication, and the inhibition of vaccinia virus RNA and DNA synthesis by camptothecin, a specific inhibitor of cellular topoisomerase, has been reported (36).…”
Section: Discussionmentioning
confidence: 95%
“…A role of the poxvirus topoisomerase in homologous DNA recombination is also unlikely on the grounds that late gene expression is not required (28,35). Our experiments do not exclude a role for a cellular topoisomerase in transcription or replication, and the inhibition of vaccinia virus RNA and DNA synthesis by camptothecin, a specific inhibitor of cellular topoisomerase, has been reported (36).…”
Section: Discussionmentioning
confidence: 95%
“…Results indicated that CPT inhibited DNA synthesis in HeLa cells at a concentration of 10 μM. Inhibition of viral DNA synthesis was observed when CPT was added 1 or 2 hr after infection . Priel et al reported that noncytotoxic doses of CPT inhibited HIV replication in acute infection of H9 cells at a high efficacy (>90%).…”
Section: Biological Activity Of Cpt and Related Derivativesmentioning
confidence: 99%
“…Inhibition of viral DNA synthesis was observed when CPT was added 1 or 2 hr after infection. 89 Priel et al 90 reported that noncytotoxic doses of CPT inhibited HIV replication in acute infection of H9 cells at a high efficacy (>90%). Moreover, CPT inhibited equine infectious anemia virus (EIAV) replication in chronically infected Cf2Th cells.…”
Section: B Antiviral Activitymentioning
confidence: 99%
“…This remarkable achievement was published in 1966 in the Journal of the American Chemical Society, the first paper Wall, Wani and colleagues published on a natural product with anticancer potential [6]. [17,18] and others have established that the synthesis of macromolecules such as RNA, DNA and protein are inhibited by camptothecin in tumor or dividing mammalian cells. The inhibition over DNA synthesis was transient when the drug is removed.…”
Section: Camptothecinmentioning
confidence: 99%